PERAN MANUSIA DALAM PENDIDIKAN: KAJIAN PUSTAKA ATAS KONTRIBUSI, FUNGSI, DAN DINAMIKA PERAN DALAM PROSES PEMBELAJARAN DAN PENGEMBANGAN KARAKTER - Abdul Wahab Syakhrani; Isma Lutfiana Masrurah; Majidatul Hidayah (CV. Adiba Aisha Amira, 2025)
This study is a literature review that aims to examine the role of humans in education from various perspectives and relevant literature sources. The focus of the study includes the contributions of individuals as educators, students, and various other supporting roles in the learning process and character development. Through critical analysis of educational theories, previous research results, and various scientific sources, this study describes how the integral role of humans shapes the quality of education and influences learning success. The results of the study show that the active role of humans is crucial to the effectiveness of education, and that the dynamics of this role continue to evolve in line with social and technological changes. This study provides a comprehensive understanding of the central function of the human role in the modern education system.